Four mononuclear dysprosium complexes with neutral Schiff-base ligands: syntheses, crystal structures and slow magnetic relaxation behavior. Issue 4 (24th December 2021) - Yang, Hui; Liu, Shan-Shan; Meng, Yin-Shan; Zhang, Yi-Quan; Pu, Lin; Wang, Xincheng; Lin, Shijing
Abstract : Subtle modifications of neutral Schiff-base ligands lead to diverse magnetic behavior in four mononuclear Dy-based complexes. Abstract : Four mononuclear 9-coordinate Dy-based complexes, [Dy(HL 1 )2 (NO3 )3 (CH3 OH)] (1Dy ), [Dy(HL 2 )2 (NO3 )3 (H2 O)] (2Dy ), [Dy(HL 3 )3 (NO3 )3 ]·CH3 CN (3Dy ), and [Dy(HL 4 )3 (NO3 )3 ] (4Dy ), have been constructed by neutral Schiff-base ligands (1-[ N -(4-R)aminomethylidene-2( 1H )-naphthalenone, R = –Cl (HL 1 ), –NO2 (HL 2 ), –OCH3 (HL 3 ), –I (HL 4 )). By tuning the terminal substituent group of HL ligands, the number of HL ligands coordinated to the central Dy 3+ ion unexpectedly varies from 2 to 3, and the local symmetry around the Dy 3+ ion reduces from D 3h to C s . Magnetic measurements reveal that 2Dy can display single-ion magnet (SIM) behavior in zero dc field, while 1Dy, 3Dy and 4Dy show field-induced slow magnetic relaxation. Ab initio calculations were employed to elucidate magnetic anisotropy in the complexes, including g -tensors, averaged transition magnetic moments and magnetic easy axes. The difference in magnetic behaviors of the four complexes can be ascribed to the terminal substituent effect of neutral Schiff-base ligands.